EKSISTENSI MANUSIA PANCASILAIS DEWASA INI DARI PERSPEKTIF KONSEP MANUSIA PERSONALIS - Kino Nara, Kristoforus Sri Ratulayn (Sophia Dharma: Jurnal Filsafat, Agama Hindu, dan Masyarakat, 2022)
This article discuss what or who Pancasilaists are in today's context. The focus of attention in the following article is on the question of what is the nature of a Pancasilaist human and how is the existence of a Pancasilaist human being. In the current era of globalization and technological disruption, which is being accelerated by the COVID-19 pandemic, it is important to rethink your identity to Indonesia. Because of course Indonesia is not impermeable to the influence of the dynamics of global developments. The author tries to re-examine who the Pancasila people are and how they exist. The method that the author will use is to use a knife of human concept analysis in the Personalism flow. This paper can offer a new interpretation and perspective on Pancasila and what a Pancasilaist human looks like when viewed from the perspective of Personalism.